Análise de parabenos em águas superficiais urbanas por extração em fase sólida on-line usando cromatografia líquida acoplada à espectrometria de massas - Triano, Simone Pereira do Nascimento (2017)
Parabens are the most popular antimicrobials used for more than 100 years in personal care products, the most known are methylpaben, ethylparaben, propylparaben and butylparaben. The continued release of these antimicrobials turned them into corganic pollutants. Therefore, methods that allow quantification at low limits are important. The present study discusses the development and validation of the analytical method by direct injection of samples into solid phase extraction using liquid chromatography coupled to the mass spectrometer for determination at low levels in spring water and waste water (ng/L) from the city of São Carlos - SP. Methylparaben at 20.0 ng/L was found in river water sample from latitude 22°00’68”S, longitude: 47°90’47”W ; methylparaben at 18.0 ng/L and butylparaben 4.1 ng/L were found in urban water sample latitude: 22°02’21”S, longitude: 47°91’40”W around Monjolinho River. The attractiveness of the developed method consists of the low volume of samples and solvents required for analyses. The four parabens were quantified in the native matrix in a total run time of 9.5 min.